Hamstring strain injury prevention: current beliefs and practices of practitioners working in major league baseball - Lazarczuk, S. L.; Headrick, J.; Hickey, J. T.; Timmins, R. G.; Leva, F. A.; Bourne, M. N. (Journal of Athletic Training, 2024)
Context: Hamstring strain injury (HSI) is the most frequently sustained injury in Major League Baseball (MLB). However, the beliefs and practices of practitioners working in MLB regarding HSI risk factors and prevention strategies in baseball athletes have not been documented. Objective: To document the current beliefs and practices of practitioners working in MLB regarding HSI prevention. Design: Cross-sectional study. Setting: Major League Baseball via an online survey. Patients or Other Participants: Athletic trainers, physical therapists, and strength and conditioning coaches working in MLB during the 2021 season. Data Collection and Analysis: An online survey was conducted, with participants completing the survey once. Questions pertained to risk factor identification, the use and perceived effectiveness of prevention strategies, and barriers to implementation. Descriptive statistics were calculated for each question. Results: A total of 91 responses were received featuring respondents from 28 of 30 MLB organizations. The perceived most important intrinsic risk factors were tolerance to high-speed running for first-time HSI and previous HSI for recurrent injury. The perceived most important extrinsic risk factor for both first-time and recurrent HSI was internal communication between staff. The perceived most effective prevention strategies were managing overall workload, regular exposure to high-speed running, and periodization. The most used prevention strategies were core or lumbopelvic strengthening, traditional resistance-training exercises, and managing overall workload. Approximately half (53%) of respondents reported barriers to effective implementation of HSI prevention strategies, including player and coach buy-in, compliance, workload management, and scheduling. Conclusions: This was the first survey to investigate MLB practitioner beliefs and practices regarding HSI prevention. Responses from practitioners regarding their beliefs about risk factors and appropriate prevention strategies varied, and discrepancies existed between the perceived most effective strategies and those most frequently used.